Analisis Kesiapan Kerja Mahasiswa Tingkat Akhir BK dan Penjaskesrek - Hani Nurrofifah; Ratna Widiastuti; Shinta Mayasari (ALIBKIN (Jurnal Bimbingan Konseling), 2018)
This study aimed to analyze of employability on final-year students of the Guidance and Counseling and Physical Education, Faculty of Teacher Training and Education University of Lampung. This research method was quantitative descriptive, with the technique analyze of percentage and Rasch model. The sample of this research from the Guidance and Counseling were 49 students, while from the Physical Education were 32 students. The results showed that Guidance and Counseling and Physical Education students had high employability results, namely at 91% for Guidance and Counseling and the Physical Education get 86%, then what needs to be improved the final-year students from the Guidance and Counseling is high order thinking skills, while the Physical Education self control. Because most of the results of the scale show high, it can be concluded that the work readiness soft skills for the final-year students from the Guidance and Counseling and the Physical Education are high.Penelitian ini bertujuan untuk menganalisis soft skills kesiapan kerja mahasiswa tingkat akhir program studi BK dan Penjaskesrek FKIP Unila. Metode penelitian ini bersifat kuantitatif deskriptif, dengan teknik analisis data Persentase dan Rasch model. Hasil penelitian menunjukkan bahwa mahasiswa program studi BK dan Penjaskesrek memiliki hasil kesiapan kerja yang tinggi, yaitu BK 91% dan Penjaskesrek mendapatkan hasil 86%, lalu yang perlu ditingkatkan pada mahasiswa tingkat akhir BK yaitu high order thinking skills sedangkan Penjaskesrek self control. Karena sebagian besar hasil skala menunjukkan tinggi, maka dapat disimpulkan bahwa soft skills kesiapan kerja mahasiswa tingkat akhir program studi BK dan Penjaskesrek tinggi. Kata kunci: bimbingan dan konseling, kesiapan kerja, penjaskesrek